A multifunctional electrolyte additive-based photocharging zinc-ion battery

CN122931173APending Publication Date: 2026-10-16DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611125549.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有多数电解液添加剂主要针对恒流或恒压充电条件下的锌负极问题进行设计,其作用机理和调控效果往往难以适应光充电条件下的非稳态充电工况

Benefits of technology

[0024](1) This invention addresses the interface failure problem faced by the zinc anode under unsteady polarization conditions during photocharging. Unlike traditional zinc-ion battery additives that are only applicable to constant current or constant voltage charging conditions, this invention maintains stable and effective interface regulation capabilities under photocharging conditions. This invention uses organic compounds containing at least disulfide bonds (S-S) and amino functional groups as additives for the electrolyte of photocharging zinc-ion batteries. During photocharging (corresponding to the zinc ion deposition process), these additives break the S-S bonds on the surface of the zinc anode through the molecules, forming Zn-S bonds on the surface of the zinc anode. At the same time, their amino functional groups act as ligand sites for zinc ions, working synergistically with the Zn-S bonds to construct an ion-selective self-assembled layer on the surface of the zinc anode in situ, effectively alleviating the instability problem of the zinc anode exacerbated by light. The Zn-S bond self-assembled layer formed on the zinc anode can reduce the direct contact between active water molecules and the zinc anode, suppressing interfacial side reactions under photocharging; it can also guide zinc ions to diffuse two-dimensionally along the (002) crystal plane, promoting uniform layered deposition, thereby suppressing dendrite growth. Meanwhile, the amino functional group forms an interfacial pH buffer effect through reversible protonation and deprotonation processes, suppressing the sudden increase in local pH caused by the hydrogen evolution reaction intensified by photocharging, thereby reducing the formation of alkaline byproducts. The synergistic effect of S-S bonds and amino functional groups significantly improves the reversibility and cycle stability of the zinc deposition/stripping process, overcoming the problem that existing single-functional additives cannot achieve synergistic suppression of multiple failure mechanisms under photocharging conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931173A_ABST
    Figure CN122931173A_ABST
Patent Text Reader

Abstract

A kind of light charging zinc ion battery based on multifunctional electrolyte additive belongs to the technical field of light storage battery.The light charging zinc ion battery includes photovoltaic unit and aqueous zinc ion battery unit, wherein: photovoltaic unit is used to provide electrical energy under light condition;The aqueous zinc ion battery unit includes at least zinc negative electrode, positive electrode and aqueous electrolyte;The photovoltaic unit and the aqueous zinc ion battery unit are integrated by sharing electrode;Wherein, the aqueous electrolyte contains multifunctional electrolyte additive, the multifunctional electrolyte additive is at least an organic compound containing disulfide bond and amino functional group, the organic compound can be adsorbed on the surface of zinc negative electrode and form selective self-assembly layer in situ, the multifunctional electrolyte additive is used to regulate the reaction behavior of zinc negative electrode and aqueous electrolyte interface under light charging condition, to inhibit hydrogen evolution reaction, corrosion behavior and dendrite growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaic and energy storage battery coupling technology, specifically relating to a photochargeable zinc-ion battery based on a multifunctional electrolyte additive. Background Technology

[0002] Solar energy is one of the most abundant renewable energy sources. Developing efficient solar energy utilization technologies is crucial for promoting carbon neutrality and a renewable energy society. Photovoltaic cells play a vital role in solar energy collection and conversion. However, due to the intermittent and unstable nature of solar radiation, photovoltaic cells cannot provide continuous and stable power output. Therefore, developing photovoltaic charging energy storage devices that integrate photovoltaic and energy storage systems is of great significance for achieving efficient solar energy collection, conversion, and storage to ensure a continuous and stable power supply.

[0003] Among various metal-based ion batteries, aqueous zinc-ion batteries are preferred due to their low cost and high theoretical capacity. With its advantages such as low redox potential and outstanding intrinsic safety, aqueous zinc-ion batteries have shown unique potential in photovoltaic-energy storage integrated applications. However, during photovoltaic charging, aqueous zinc-ion batteries still face a series of technical problems that urgently need to be solved, especially the insufficient stability of the interface between the zinc anode and the aqueous electrolyte. Affected by the intermittent nature of sunlight, light fluctuations, and the output instability of photovoltaic devices, the zinc anode often experiences high instantaneous current density and unsteady polarization during photovoltaic charging, which significantly aggravates the side reaction kinetics at the interface between the zinc anode and the aqueous electrolyte, making problems such as hydrogen evolution reaction, zinc corrosion, and dendrite growth more prominent, thereby weakening the reliability of photovoltaic-energy storage integrated systems.

[0004] Currently, strategies for improving the stability of zinc anodes mainly include interface modification, structural design, membrane modification, and electrolyte additives. Among these, electrolyte additives have attracted widespread attention due to their advantages of ease of operation, low cost, and ease of scalability. However, most existing electrolyte additives are designed primarily for zinc anode problems under constant current or constant voltage charging conditions, and their mechanisms of action and regulatory effects are often difficult to adapt to the unsteady charging conditions under photocharging. Currently, research on electrolyte additives for photocharging zinc ion systems is still very limited.

[0005] Furthermore, in conventional zinc-ion batteries, electrolyte additives, represented by small organic molecules, can guide zinc deposition and suppress dendrite formation to some extent through interfacial adsorption. However, these additives only address single issues; simple interfacial modulation is insufficient to form a stable interface and cope with the multiple interfacial challenges exacerbated by light during photocharging. The synergistic effect of multiple additives might solve these problems, but this would undoubtedly increase the complexity of the system. Therefore, there is an urgent need to develop multifunctional electrolyte additives capable of synergistically regulating the zinc anode interfacial reaction under photocharging conditions to address the stability issues of the zinc anode in photo-electric coupling environments and promote the practical application of this technology. Summary of the Invention

[0006] To address the aforementioned problems, this invention proposes a photochargeable zinc-ion battery based on a multifunctional electrolyte additive. During photocharging (corresponding to the zinc ion deposition process), the S-S bonds in the additive molecules break on the zinc anode surface, generating sulfur-containing active groups that interact with the zinc anode to form Zn-S bonds. Simultaneously, its amino functional groups act as zinc ion ligand sites, synergistically interacting with the Zn-S bonds to construct an ion-selective self-assembled layer on the zinc anode surface, effectively mitigating the instability of the zinc anode exacerbated by light exposure. The S-S bond breakage in this additive generates sulfur-containing active groups, forming a Zn-S bond self-assembled layer on the zinc anode. This not only reduces direct contact between active water and the zinc anode, suppressing interfacial side reactions under photocharging, but also guides zinc ions to diffuse two-dimensionally along the (002) crystal plane, promoting uniform layered deposition and thus suppressing dendrite growth. Furthermore, the amino functional groups, through reversible protonation and deprotonation processes, form an interfacial pH buffer effect, suppressing the local pH surge caused by the hydrogen evolution reaction, thereby reducing the generation of alkaline byproducts. The synergistic effect of S-S bonds and amino functional groups significantly improves the reversibility and cycle stability of the zinc deposition / stripping process, providing a feasible path for efficient and stable photochargeable zinc-ion batteries.

[0007] This invention has advantages such as simple process, low cost and environmental friendliness, and can significantly improve the long-term cycle stability of photochargeable zinc-ion batteries, providing a promising solution for their commercial application.

[0008] To achieve the above objectives, the technical solution provided by the present invention is as follows:

[0009] A photo-chargeable zinc-ion battery based on a multifunctional electrolyte additive is disclosed. The photo-chargeable zinc-ion battery includes a photovoltaic unit and an aqueous zinc-ion battery unit. The photovoltaic unit provides electrical energy under illumination. The aqueous zinc-ion battery unit includes at least a zinc anode, a cathode, and an aqueous electrolyte. The photovoltaic unit and the aqueous zinc-ion battery unit are integrated via a shared electrode. The aqueous electrolyte contains a multifunctional electrolyte additive, which is an organic compound containing at least two disulfide bonds (S-S) and amino functional groups. This organic compound can undergo directional adsorption on the zinc anode surface and form a selectively self-assembled layer in situ. The multifunctional electrolyte additive is used to regulate the reaction behavior at the interface between the zinc anode and the aqueous electrolyte under photocharging conditions to suppress hydrogen evolution reaction, corrosion, and dendrite growth.

[0010] Furthermore, the multifunctional electrolyte additive is an organic compound that simultaneously contains at least disulfide bonds (S-S) and amino functional groups; the organic compound can undergo directional adsorption on the zinc anode surface and form a selective self-assembled layer in situ.

[0011] Furthermore, the organic compound has the following general formula:

[0012] R1─S─S─R2

[0013] R1 and R2 may be the same or different, and are independently selected from C1-C10 straight-chain or branched alkyl groups or C3-C10 cycloalkyl groups containing at least one amino functional group.

[0014] Furthermore, the amino functional group is selected from at least one of primary amino (-NH2), secondary amino (-NH-) or tertiary amino, preferably primary amino.

[0015] Further, the multifunctional electrolyte additive is selected from one or more combinations of cystine, 2,2'-dithiobis(ethylamine), dithiobis(3-aminopropane), dithiobis(6-aminohexane), 4,4'-diaminodiphenyl disulfide, 2,2'-diaminodiphenyl disulfide, dithiobis(2-aminobenzamide), and their derivatives; the concentration of the multifunctional electrolyte additive in the electrolyte is [missing information]. Preferred .

[0016] Furthermore, the S-S bonds in the multifunctional electrolyte additive break on the zinc anode surface and form Zn-S bonds on the zinc anode; at the same time, the amino functional groups in the multifunctional electrolyte additive serve as zinc ion selective sites and work synergistically with the Zn-S bonds to construct an ion-selective self-assembled layer in situ on the zinc anode surface.

[0017] Furthermore, the selective self-assembly layer can regulate the interfacial transport behavior of zinc ions and reduce the probability of free water participating in the electrode interfacial reaction.

[0018] Furthermore, during the photocharging process, the multifunctional electrolyte additive can alleviate the interfacial side reactions caused by fluctuations in photocurrent density or unsteady polarization of the zinc anode.

[0019] Furthermore, the solvent of the aqueous electrolyte is deionized water, and the electrolyte is at least one of the following soluble zinc salts: zinc sulfate, zinc chloride, zinc tetrachloride, zinc nitrate, zinc bromide, zinc trifluoromethanesulfonate, zinc bis(trifluoromethanesulfonyl)imide, zinc acetate, and their hydrates, with a concentration of [missing information]. Preferred .

[0020] Furthermore, the photovoltaic unit is selected from one or more combinations of silicon-based photovoltaic cells, compound thin-film photovoltaic cells, perovskite, dye-sensitized, and organic photovoltaic cells.

[0021] Furthermore, the positive electrode material of the aqueous zinc-ion battery unit is selected from manganese dioxide, vanadium-based oxides, Prussian blue and their analogues or organic positive electrode materials, and the zinc negative electrode is at least one of zinc plate, zinc sheet, zinc foil, three-dimensional zinc foam, and zinc-based composite materials.

[0022] Furthermore, the application of the aforementioned multifunctional electrolyte additive in photochargeable zinc-ion batteries.

[0023] Compared with the prior art, the present invention has the following advantages and technical effects:

[0024] (1) This invention addresses the interface failure problem faced by the zinc anode under unsteady polarization conditions during photocharging. Unlike traditional zinc-ion battery additives that are only applicable to constant current or constant voltage charging conditions, this invention maintains stable and effective interface regulation capabilities under photocharging conditions. This invention uses organic compounds containing at least disulfide bonds (S-S) and amino functional groups as additives for the electrolyte of photocharging zinc-ion batteries. During photocharging (corresponding to the zinc ion deposition process), these additives break the S-S bonds on the surface of the zinc anode through the molecules, forming Zn-S bonds on the surface of the zinc anode. At the same time, their amino functional groups act as ligand sites for zinc ions, working synergistically with the Zn-S bonds to construct an ion-selective self-assembled layer on the surface of the zinc anode in situ, effectively alleviating the instability problem of the zinc anode exacerbated by light. The Zn-S bond self-assembled layer formed on the zinc anode can reduce the direct contact between active water molecules and the zinc anode, suppressing interfacial side reactions under photocharging; it can also guide zinc ions to diffuse two-dimensionally along the (002) crystal plane, promoting uniform layered deposition, thereby suppressing dendrite growth. Meanwhile, the amino functional group forms an interfacial pH buffer effect through reversible protonation and deprotonation processes, suppressing the sudden increase in local pH caused by the hydrogen evolution reaction intensified by photocharging, thereby reducing the formation of alkaline byproducts. The synergistic effect of S-S bonds and amino functional groups significantly improves the reversibility and cycle stability of the zinc deposition / stripping process, overcoming the problem that existing single-functional additives cannot achieve synergistic suppression of multiple failure mechanisms under photocharging conditions.

[0025] (2) The electrolyte additive for photo-chargeable zinc-ion batteries of the present invention contains organic compounds containing at least disulfide bonds (S-S) and amino functional groups, which can significantly improve the cycle life of photo-chargeable zinc-ion batteries. When used in conjunction with high-performance solar cells, it can effectively delay the capacity decay of photo-storage batteries, which is of great significance for building efficient and long-life photo-chargeable zinc-ion batteries. Attached Figure Description

[0026] Figure 1 Comparison of charge-discharge cycle performance of Zn||Zn symmetric batteries constructed using the electrolyte systems prepared in Example 1, Comparative Examples 1 and 2.

[0027] Figure 2 The contact angle between the Zn anode and H2O in the Zn||Zn symmetric cells constructed using the electrolyte systems prepared in Example 1, Comparative Examples 1 and 2 is compared after one cycle.

[0028] Figure 3 Comparison of charge-discharge cycle performance of Zn||Cu asymmetric batteries constructed using the electrolyte systems prepared in Example 1, Comparative Examples 1 and 2.

[0029] Figure 4Comparison of cyclic voltammetry curves of Si / V2O5||Zn photocharged zinc-ion batteries constructed using the electrolyte systems prepared in Example 1, Comparative Examples 1 and 2.

[0030] Figure 5 Comparison of photocharge / discharge cycle performance of Si / V2O5||Zn photocharged zinc-ion batteries constructed using the electrolyte systems prepared in Example 1, Comparative Examples 1 and 2.

[0031] Figure 6 SEM images of the zinc anode after cycling of the Si / V2O5||Zn photocharged zinc-ion batteries constructed using the electrolyte systems prepared in Example 1, Comparative Examples 1 and 2. Detailed Implementation

[0032] The present invention is described in detail below with reference to the embodiments, but the present invention is not limited to these embodiments. Unless otherwise specified, the raw materials and reagents used in the embodiments are commercially available.

[0033] Example 1

[0034] A photochargeable zinc-ion battery based on a multifunctional electrolyte additive, wherein the additive is 2,2'-dithiobis(ethylamine). Zn||Zn symmetric cells and Zn||Cu asymmetric cells were prepared using the above electrolyte additive. The effect of the 2,2'-dithiobis(ethylamine) electrolyte additive on improving the reversibility and cycle stability of the zinc deposition / stripping process was tested. Furthermore, in the photochargeable zinc-ion battery prepared using the above multifunctional electrolyte additive, the effect of the 2,2'-dithiobis(ethylamine) electrolyte additive on improving the photocharge / discharge cycle stability of the photochargeable zinc-ion battery was tested.

[0035] 1) Preparation of aqueous electrolyte

[0036] Using deionized water as solvent and zinc trifluoromethanesulfonate as electrolyte, the solution was prepared by stirring and dissolving. Aqueous solution of zinc trifluoromethanesulfonate. Add 2,2'-dithiobis(ethylamine) additive to the prepared aqueous solution of zinc trifluoromethanesulfonate, and adjust the concentration to [missing information]. After stirring and dissolving, a photochargeable zinc-ion battery electrolyte is obtained.

[0037] 2) Preparation of Zn||Zn symmetric cells

[0038] Clean zinc foil with a thickness of 100 micrometers is selected, sanded, and cut into 12 mm diameter circular pieces to be used as electrodes of the symmetrical battery. A glass fiber membrane is used as a separator, and the above-mentioned electrolyte is used to encapsulate the CR2025 coin cell. The assembly sequence of the coin cell is positive electrode shell, gasket, zinc foil, separator, zinc foil, gasket, spring, and negative electrode shell.

[0039] The Zn||Zn symmetric battery was subjected to charge-discharge cycle testing on the Xinwei Battery Testing System, with a working current density of [missing value]. Surface capacity is When a potential abrupt change is observed, the time point of the abrupt change is taken as the short-circuit time of the symmetrical cell.

[0040] After one cycle of the Zn||Zn symmetrical cell, the Zn negative electrode was removed, and the contact angle between H2O and the cycled Zn negative electrode was measured.

[0041] 3) Preparation of Zn||Cu asymmetric cells

[0042] Clean copper foil with a thickness of 20 micrometers is selected and cut into 12 mm diameter discs for use as the positive electrode of the asymmetric battery; clean zinc foil with a thickness of 100 micrometers is selected, polished with sandpaper, and cut into 12 mm diameter discs for use as the negative electrode of the asymmetric battery. A glass fiber membrane is used as the separator, and the above-mentioned electrolyte is used to encapsulate the CR2025 coin cell. The assembly sequence of the coin cell is: positive electrode shell, gasket, copper foil, separator, zinc foil, gasket, spring, negative electrode shell.

[0043] The Zn||Cu asymmetric battery was subjected to charge-discharge cycle testing on the Xinwei Battery Testing System, with a discharge current density of [missing value]. Surface capacity is The charging current density is Cutoff voltage see Figure 3 As shown. When a potential abrupt change is observed, the time point of the abrupt change is taken as the short-circuit time of the asymmetric cell.

[0044] 4) Preparation of photo-chargeable zinc-ion batteries

[0045] Commercial crystalline silicon solar cells with an output voltage of approximately 2.1 V were selected as photovoltaic units. Commercial V₂O₅ active material, Ketjen Black conductive agent, and polyvinylidene fluoride binder were mixed in a mass ratio of 7:2:1, ground in an agate mortar for 15 minutes, followed by the addition of an appropriate amount of N-methylpyrrolidone and further grinding for another 15 minutes to prepare a uniform slurry. The slurry was uniformly coated onto one side of a titanium foil using a scraper and dried at 60°C for 12 hours to obtain the V₂O₅ cathode. The dried V₂O₅ cathode was cut into 12 mm diameter discs, and silver paste was coated onto the back side of the titanium foil substrate. This was then bonded and integrated with the positive electrode of the solar cell to construct a composite shared photocathode. A glass fiber separator was placed above the shared photocathode. Clean zinc foil with a thickness of 100 micrometers was selected, sanded, and cut into 14 mm diameter discs. These discs were placed above the separator as the zinc-ion cell anode; finally, a 2 cm × 2 cm glass substrate was placed on top as the final plate. A hot melt glue gun was used to initially fix the separator, zinc sheet, and glass substrate, and injection holes were pre-drilled on the side of the structure. After the colloid cooled and solidified, the electrolyte was added dropwise through the injection holes using a syringe until the V2O5 active material and separator were fully wetted. Finally, the injection holes were sealed with a hot melt glue gun, completing the encapsulation of the three-electrode Si / V2O5||Zn photochargeable zinc-ion battery.

[0046] The Si / Zn‖V2O5 photo-chargeable zinc-ion battery was placed under a 150 W xenon lamp, with the light source directly illuminating the solar cell's light-receiving surface. The electrochemical performance and photo-charge / discharge cycle tests of the photo-chargeable zinc-ion battery were tested on the Chenhua electrochemical workstation, and the zinc anode after cycling was characterized and analyzed by SEM.

[0047] Comparative Example 1

[0048] The difference between this comparative example and Example 1 is that the additive is cysteine, while the rest of the preparation process is the same as in Example 1. A zinc trifluoromethanesulfonate aqueous electrolyte was prepared, and Zn||Zn symmetric cells and Zn||Cu asymmetric cells were assembled. Charge-discharge cycle tests and contact angle tests of the Zn anode were conducted. In addition, Si / V2O5||Zn photochargeable zinc-ion cells were assembled, and electrochemical performance and photocharge / discharge cycle tests were conducted. The zinc anode after cycling was characterized by SEM.

[0049] Comparative Example 2

[0050] The difference between this comparative example and Example 1 is that the concentration of the multifunctional electrolyte additive was adjusted to 0, while the rest of the preparation process was the same as in Example 1, resulting in... A zinc trifluoromethanesulfonate aqueous electrolyte was prepared, and Zn||Zn symmetric cells and Zn||Cu asymmetric cells were assembled. Charge-discharge cycle tests and contact angle tests of the Zn anode were conducted. In addition, Si / V2O5||Zn photochargeable zinc-ion cells were assembled, and electrochemical performance and photocharge / discharge cycle tests were conducted. The zinc anode after cycling was characterized by SEM.

[0051] Figure 1 The charge-discharge cycle performance of Zn||Zn symmetric batteries constructed using the electrolyte systems prepared in Example 1, Comparative Example 1, and Comparative Example 2 was compared. Test results showed that the Zn||Zn symmetric battery assembled in Example 1 cycled stably for 1100 h, while Comparative Example 1 and Comparative Example 2 experienced short circuits after 960 h and 28 h, respectively. Compared to cysteine ​​additives containing thiol and amino functional groups, the 2,2'-dithiobis(ethylamine) used in Example 1 contains both disulfide bonds and amino functional groups. It is speculated that its disulfide bonds facilitate in-situ activation at the zinc anode interface and may form a Zn–S bond-rich interfacial protective layer, thereby aiding in the regulation of… The deposition behavior is improved, and zinc dendrite growth is inhibited. Simultaneously, the amino functional groups may mitigate pH fluctuations caused by hydrogen dissolution reactions and reduce the formation of alkaline byproducts by regulating the local acid-base environment at the interface. Compared to cysteine, which directly contains thiol and amino functional groups, additives containing disulfide bonds may act as interfacial active precursors, which is more conducive to constructing a stable and durable interfacial protective layer and improving the reversibility of the zinc deposition / dissolution process. Therefore, Example 1 exhibits superior cycling stability.

[0052] Figure 2 This study compares the water contact angle of the Zn||Zn symmetric cells assembled using the electrolyte systems prepared in Example 1, Comparative Example 1, and Comparative Example 2 after one cycle. The test results show that the water contact angle of the Zn anode surface in Example 1 is 97.6°, significantly higher than the 86.0° and 72.9° of Comparative Example 1 and Comparative Example 2, respectively, indicating stronger hydrophobicity of the Zn anode surface in Example 1. This is presumably due to the adsorption of 2,2'-dithiobis(ethylamine) at the zinc anode interface, which may form a more stable sulfur-containing interface layer through interfacial activation of disulfide bonds, thereby increasing the hydrophobicity of the Zn anode surface. Higher hydrophobicity helps reduce direct contact between water molecules and the Zn anode, thus inhibiting hydrogen evolution reaction and other water-related interfacial side reactions, and improving the stability of the zinc anode interface. Compared to cysteine, which directly contains thiol and amino functional groups, 2,2'-dithiobis(ethylamine), which contains disulfide bonds and amino functional groups, is more conducive to forming a stable and durable interfacial protective layer, thus exhibiting superior interfacial hydrophobic properties.

[0053] Figure 3This study compares the charge-discharge cycle performance of Zn||Cu asymmetric batteries assembled using the electrolyte systems prepared in Example 1, Comparative Example 1, and Comparative Example 2. Test results show that the Zn||Cu asymmetric battery assembled in Example 1 can cycle stably for 500 h while maintaining a high and stable coulombic efficiency of 99.4%. Comparative Example 1 experienced a short circuit after 420 h of cycling, with a coulombic efficiency of approximately 98.2%. Comparative Example 2 experienced a short circuit after 15 h of cycling, with a coulombic efficiency of only about 66.3%, and exhibited significant fluctuations during cycling. These results indicate that the 2,2'-dithiobis(ethylamine) used in Example 1 can significantly improve the reversibility of the Zn deposition / stripping process. Compared to cysteine, which directly contains thiol and amino functional groups, 2,2'-dithiobis(ethylamine), containing disulfide bonds and amino functional groups, may be more beneficial in maintaining the long-term stability of the zinc anode interface and improving the reversibility of the Zn deposition / stripping process, thus exhibiting higher coulombic efficiency and superior cycle stability.

[0054] Figure 4 Cyclic voltammetry (CV) curves of Si / V₂O₅||Zn photochargeable zinc-ion batteries constructed using the electrolyte systems prepared in Example 1, Comparative Example 1, and Comparative Example 2 are compared. The test results show that, compared to Comparative Example 1 and Comparative Example 2, the CV curve of Example 1 exhibits a higher redox peak current and a larger enclosing area, indicating that the photochargeable zinc-ion battery assembled in Example 1 has higher electrochemical activity and charge storage capacity. It is speculated that this is because the disulfide bond and amino functional group in 2,2'-dithiobis(ethylamine) synergistically improve the stability of the zinc anode interface, weaken the hydrogen evolution reaction and dendrite growth at the zinc anode, and improve the reversibility of the Zn deposition / stripping process, thereby reducing battery polarization and promoting… The reversible transport and electrode reaction processes in Example 1 demonstrate superior electrochemical reaction kinetics.

[0055] Figure 5 A comparison of the photocharge / discharge cycle performance of Si / V₂O₅||Zn photochargeable zinc-ion batteries assembled using the electrolyte systems prepared in Example 1, Comparative Example 1, and Comparative Example 2 is presented. Test results show that the photochargeable zinc-ion battery assembled in Example 1 exhibits excellent cycle stability, with an initial specific capacity of [missing value]. It still maintains approximately after 300 cycles. The discharge specific capacity. In contrast, the initial specific capacity of the battery in Comparative Example 1 is... After 300 cycles, the capacity only remains Comparative Example 2 showed rapid capacity decay after only 5 stable cycles, and a short circuit occurred at the 49th cycle. This is presumably because the disulfide bonds in 2,2'-dithiobis(ethylamine) facilitate in-situ activation at the zinc anode interface, potentially forming a relatively stable sulfur-containing interfacial protective layer. Simultaneously, the amino functional groups may help buffer the local acid-base environment at the interface, thereby synergistically improving the reversibility of the Zn deposition / stripping process, suppressing interfacial side reactions such as zinc dendrite growth and hydrogen evolution, and delaying the failure of the zinc anode during photocharging cycling. In contrast, although cysteine ​​containing thiol and amino functional groups can directly coordinate with Zn, its free thiol groups have high activity, suggesting that it is more prone to oxidation or gradual consumption during long-term cycling, thus weakening the interfacial protective effect with each cycle. Therefore, Example 1 exhibited superior capacity retention and cycling stability.

[0056] Figure 6 SEM images of the zinc anodes in Si / V₂O₅||Zn photocharged zinc-ion batteries constructed using the electrolyte systems prepared in Example 1, Comparative Example 1, and Comparative Example 2, after cycling. The test results show that the zinc anode in Example 1, after 300 photocharge / discharge cycles, still has a relatively smooth and dense surface with no obvious zinc dendrites observed. In contrast, the zinc anode in Comparative Example 1 showed uneven zinc deposition and a small amount of zinc dendrites after 300 cycles, while the zinc anode in Comparative Example 2 showed extensive zinc dendrite growth after only 49 cycles, ultimately leading to a short circuit. Based on the aforementioned electrochemical test results, it is speculated that the disulfide bonds and amino functional groups in 2,2'-dithiobis(ethylamine) can synergistically improve the interfacial stability of the zinc anode. The disulfide bonds may facilitate in-situ activation at the zinc anode interface and the formation of a stable sulfur-containing interfacial layer, while the amino functional groups may help regulate the local acid-base environment at the interface, jointly promoting… Uniform deposition suppresses side reactions such as zinc dendrite growth and hydrogen evolution, improves the reversibility of the Zn deposition / stripping process, and thus significantly enhances the cycle stability of the zinc anode in photovoltaic zinc-ion batteries.

[0057] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A photochargeable zinc-ion battery based on a multifunctional electrolyte additive, characterized in that, The photo-chargeable zinc-ion battery includes a photovoltaic unit and an aqueous zinc-ion battery unit, wherein: the photovoltaic unit provides electrical energy under illumination; the aqueous zinc-ion battery unit includes at least a zinc negative electrode, a positive electrode, and an aqueous electrolyte; the photovoltaic unit and the aqueous zinc-ion battery unit are integrated through a shared electrode; wherein the aqueous electrolyte contains a multifunctional electrolyte additive, which is an organic compound containing at least disulfide bonds and amino functional groups, the organic compound being able to undergo directional adsorption on the zinc negative electrode surface and form a selective self-assembled layer in situ, the multifunctional electrolyte additive being used to regulate the reaction behavior of the zinc negative electrode and aqueous electrolyte interface under photocharging conditions, so as to inhibit hydrogen evolution reaction, corrosion behavior, and dendrite growth.

2. The photo-chargeable zinc-ion battery according to claim 1, characterized in that, The organic compound has the following general formula: R1─S─S─R2 R1 and R2 may be the same or different, and are independently selected from C1-C10 straight-chain or branched alkyl groups or C3-C10 cycloalkyl groups containing at least one amino functional group.

3. The photo-chargeable zinc-ion battery according to claim 2, characterized in that, The amino functional group is selected from at least one of primary amino, secondary amino, or tertiary amino groups.

4. The photo-chargeable zinc-ion battery according to any one of claims 1-3, characterized in that, The multifunctional electrolyte additive is selected from one or more of cystine, 2,2'-dithiobis(ethylamine), dithiobis(3-aminopropane), dithiobis(6-aminohexane), 4,4'-diaminodiphenyl disulfide, 2,2'-diaminodiphenyl disulfide, dithiobis(2-aminobenzamide), and their derivatives; the concentration of the multifunctional electrolyte additive in the aqueous electrolyte is [missing information]. .

5. The photo-chargeable zinc-ion battery according to claims 1-4, characterized in that, The S-S bonds in the multifunctional electrolyte additive break on the zinc anode surface, and the resulting sulfur-containing active groups interact with the zinc anode to form Zn-S bonds. At the same time, the amino functional groups in the multifunctional electrolyte additive act as zinc ion ligand sites, and work synergistically with the Zn-S bonds to construct an ion-selective self-assembled layer in situ on the zinc anode surface.

6. The photo-chargeable zinc-ion battery according to claims 1-5, characterized in that, The selective self-assembly layer can regulate the interfacial transport behavior of zinc ions and reduce the probability of free water participating in the electrode interfacial reaction.

7. The photo-chargeable zinc-ion battery according to claims 1-6, characterized in that, During photocharging, the multifunctional electrolyte additive can alleviate interfacial side reactions caused by fluctuations in photocurrent density or unsteady polarization of the zinc anode.

8. The photochargeable zinc-ion battery electrolyte according to claims 1-7, characterized in that, The solvent of the aqueous electrolyte is deionized water, and the electrolyte is at least one of zinc sulfate, zinc chloride, zinc tetrachloride, zinc nitrate, zinc bromide, zinc trifluoromethanesulfonate, zinc bis(trifluoromethanesulfonyl)imide, zinc acetate, and their hydrates, with a concentration of [missing information]. .

9. The photochargeable zinc-ion battery according to any one of claims 1-8, characterized in that, The photovoltaic unit is selected from one or more combinations of silicon-based photovoltaic cells, compound thin-film photovoltaic cells, perovskite, dye-sensitized, and organic photovoltaic cells.

10. The photochargeable zinc-ion battery according to any one of claims 1-9, characterized in that, The positive electrode material of the aqueous zinc-ion battery unit is selected from manganese dioxide, vanadium-based oxide, Prussian blue or organic positive electrode material, and the zinc negative electrode is at least one of zinc plate, zinc sheet, zinc foil, three-dimensional zinc foam, and zinc-based composite material.